Peningkatan Kompetensi Guru dan Siswa SMK Melalui Bimtek Penyusunan Laporan Keuangan Berbasis SAK-ETAP - Reni Endang Sulastri; Ferdawati Ferdawati; Welsi Haslina; Reno Fithri Meuthia; Vioni Hidayati (Institut Nalanda, 2023)
The main competency that must be possessed by vocational school students majoring in accounting is competency in preparing financial reports, namely competency as an